Factors Influencing Investor Decisions in Follow-on Public Offerings (FPOs): Evidence from the Nepalese Emerging Capital Market - Chaulagain, Rajesh Kumar; Subedi, Saroj; Bhandari, Badri Prasad (Journal of Emerging Management Studies, 2026)
Purpose - This article examines Nepalese retail investors' FPO subscription factors. This paper uses conventional and behavioral finance to investigate the influence of company specific, behavioral, and market factors on investment decision in follow-on-public offers in the context of Nepal.Design/methodology/approach - Design in the cross-sectional survey, 395 investors in Nepal with share market expertise were surveyed. Structured questionnaire was used to collect data.  Data were analyzed using descriptive statistics, structural equation model, correlation analysis, reliability tests, and multiple regression using SPPS and AMOS-26.Findings - Market circumstances and behavioral factors positively affect FPO investment choices, but company-specific variables lose relevance in multivariate analysis. Behavioral aspects have the most important impact, demonstrating that investor psychology, peer effect as well as prior experience and fear of losing out strongly affect real subscription choices. Conversely, company-related information only gains relevance at descriptive and bivariate levels; investors nevertheless accept fundamentals.Conclusion - Results exhibits that FPO investment adoption are primarily directed by behavioral heuristics rather than corporate fundamentals, suggest that investors psychology and social dynamics effectively dominant financial matrices. Subsequently, investor appear less sensible about companies’ specific factors, such as financial performance, corporate governance, and growth potentials.Implication - The study contributes to the literature on Nepal-specific stock follow-on issuance and has practical consequences for offering firms, regulators, advisers, and retail investors.Originality/value - Absence of substantial empirical evidence, this study provides an exclusive empirical analysis of FPO subscription behavior in context of Nepal by incorporating traditional and behavioral finance.